Industrial Pollution Regulation in the EU and in Macedonia, Serbia And Croatia - Chavleski, Aleksandar (Journal of Economic Development, Environment and People, 2013)
Industrial pollution control has substantial impact in the protection of the environment. In the European Union, there’s vast legislation in this field consisting mainly of the Directive on industrial emissions of 2010 aimed at consolidating the so far existing legislation in this field. The new Directive on industrial emissions aims to establish an integrated prevention and control of the pollution arising from industrial activities and it lays down rules designed to prevent or, where that is not practicable, to reduce emissions into air, water and land and to prevent the generation of waste, in order to achieve a high level of protection of the environment taken as a whole. Macedonia, Serbia and Croatia have made significant progress in this field in the recent years as part of their obligations under the Stabilization and Association Process. The purpose of this particular article is to evaluate the degree of alignment and implementation of the environmental legislation in this particular area with the legislation of EU as well its practical application, and to identify the existing deficiencies and necessary steps for action